2001
DOI: 10.1152/ajpheart.2001.280.3.h1051
|View full text |Cite
|
Sign up to set email alerts
|

Elevated capillary tube hematocrit reflects degradation of endothelial cell glycocalyx by oxidized LDL

Abstract: Proteoglycans and plasma proteins bound to the endothelial cell glycocalyx are essential for vascular function, but at the same time, they lower capillary tube hematocrit by reducing capillary volume available to flowing blood. Because oxidized low-density lipoproteins (oxLDL) reduce the effective thickness of the glycocalyx (Vink H, Constantinescu AA, and Spaan JAE. Circulation 101: 1500-1502, 2000), we designed the present study to determine whether this is caused by pathological degradation of glycocalyx co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
4
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 36 publications
9
103
4
3
Order By: Relevance
“…The presence of glycocalyx prevents RBCs from approximating the endothelium very closely. 5,21,22 Previous studies, in which microvascular glycocalyx was assessed in humans by SDF imaging of the sublingual microvasculature, 20 together with previous experimental studies 11,23 have led to the concept that perturbation of the glycocalyx is associated with an impairment of its RBCs-excluding properties, affecting the temporal and spatial variations of the microvascular RBC column width. Similarly, recent experimental studies showed that enzymatic degradation of glycocalyx is followed by increases in PBR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of glycocalyx prevents RBCs from approximating the endothelium very closely. 5,21,22 Previous studies, in which microvascular glycocalyx was assessed in humans by SDF imaging of the sublingual microvasculature, 20 together with previous experimental studies 11,23 have led to the concept that perturbation of the glycocalyx is associated with an impairment of its RBCs-excluding properties, affecting the temporal and spatial variations of the microvascular RBC column width. Similarly, recent experimental studies showed that enzymatic degradation of glycocalyx is followed by increases in PBR.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is involved in mediating shear-induced release of nitric oxide and contributes to the endothelial permeability barrier, the regulation of redox state, and the inhibition of coagulation as well as leukocyte and platelet adhesion. [6][7][8][9] Perturbation of glycocalyx occurs after provocation with inflammatory or atherogenic stimuli (such as ischemia reperfusion, 10 infusion of oxidized LDL, 9,11 administration of TNFa 12 or endotoxin, 13 and during hyperglycemia 14 ) and after stimulation with thrombin, 15 atrial natriuretic peptide, 16 or abnormal blood shear stress. 17,18 Consequences of glycocalyx perturbation include a wide range of vascular abnormalities in experimental models, including increased vascular permeability followed by generation of tissue edema, 19 increased rolling and adhesion of leukocytes, 6 and increased platelet adhesion.…”
mentioning
confidence: 99%
“…There is thinning of the glycocalyx in diabetes [2] and heterozygous familial hypercholesterolemia [9], both diseases characterised by proneness to coronary disease. Constantinescu et al [10] demonstrated thinning of the glycocalyx by oxidised LDL.…”
Section: The Importance Of Flow Mediated Arterial Dilatation (Fmd)mentioning
confidence: 99%
“…The release of inflammatory mediators induces morphological changes of the endothelium and its protective glycocalyx 30, 31. Endothelial exposure to oxidative stress, oxidized lipoproteins,32, 33, 34 and hyperglycemia35 cause further glycocalyx injury which in turn give rise to profound changes in capillary flows and hematocrit 33, 36. The glycocalyx constitutes a fluid barrier, and degradation of the glycocalyx is hence associated with edema and capillary compression 37, 38…”
Section: The Origins Of Capillary Flow Disturbances or Occlusion In Smentioning
confidence: 99%